Peran Pembentukan Etika Dan Pengendalian Diri Terhadap Pengembangan Sumber Daya Manusia (Studi Pada Smp Negeri 3 Karangploso Kab. Malang) - Muhammad Risalul Huda; Abdul Kodir Djaelani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract             In this 4.0 era ethics and self-control become one of the things needed in the generations needed to be able to compete in this era. Because ethics and self-control become one of the things that must be opened early by parents or teachers who are in school, so that the human resources or potential human resources that come have ethical values and self-control in order to improve relationships better in the future . In order to create a good and civilized society at the same time able to compete in the era of globalization.Keyword :Ethics, self-control, and human resource